Maximum-revenue versus optimum welfare export taxes - Roger Clarke; David R. Collie (Cardiff University, Cardiff Business School, 2006)
In a game between two exporting countries, both countries may be better off if they both delegate to policymakers who maximise tax revenue rather than welfare. However, both countries delegating to policymakers who maximise revenue is not necessarily a Nash equilibrium. The game may be a prisoner's dilemma where both countries are better off delegating to policymakers who maximise revenue, but both will delegate to policymakers who maximise welfare in the Nash equilibrium. This result is obtained in the Bertrand duopoly model of Eaton and Grossman (1986) and the perfectly competitive model of Panagariya and Schiff (1995).
Keywords: C72; F11; F12; F13; 330; Trade Policy; Export Taxes; Game Theory; Delegation